Influence of sex and specialty on the prediction of middle-distance running performances using the Mercier et al.`s nomogram - Coquart, J. B.; Mercier, D.; Tabben, M.; Bosquet, L. (Journal of Sports Sciences, 2015)
The aim was to test the influence of sex and specialty (3000, 5000 and 10000 m) on the validity of middle-distance running performance predictions obtained from the Mercier et al.`s nomogram. Consequently, we examined all official French track running rankings for the 3000-, 5000- and 10000-m events (men and women) from 2006 to 2012. A scoring table was used to determine the runners` specialties. Only runners who performed in the three distance events within the same year were included (75 women and 400 men). The Mercier et al.`s nomogram was used to predict one running performance from the other two. The results showed no significant difference between actual and predicted running performances (P = 0.77). Female runners had significantly lower performances than male runners (P < 0.001). Specialty did not influence performances (P = 0.11). Very high correlations were found between actual and predicted performances (0.91 < r < 0.99), with the exception of women (r = 0.85) in 5000 m. Moreover, low limits of agreement were obtained for male and female runners, whatever the specialty. These results support the validity of the nomogram to predict running performance in the 3000-, 5000- and 10000-m events for male and female runners, whatever the specialty. The predicted running performances may be used in training programmes (e.g., to prescribe tempo runs) and competitions (e.g., to establish split times).